2014
DOI: 10.1128/jvi.01863-14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Highly Diverse Gene Borders in Ebola Virus Reveals a Distinct Mechanism of Transcriptional Regulation

Abstract: Ebola virus (EBOV) belongs IMPORTANCEOur current understanding of EBOV transcription regulation is limited due to the requirement for high-containment conditions to study this highly pathogenic virus. EBOV is thought to share many mechanistic features with well-analyzed prototype nonsegmented negative-sense RNA viruses. A single polymerase entry site at the 3= end of the genome determines that transcription of the genes is mainly controlled by gene order and cis-acting signals found at the gene borders. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 78 publications
8
33
1
Order By: Relevance
“…Even though the gradient of transcription is believed to be universal for nonsegmented negative-strand viruses (50), the levels of transcription of individual genes may not necessarily follow the gradient exactly due to the regulatory role of different elements of gene junctions, which may be different for different pairs of genes. The elements, which effect transcription, include intergenic regions and transcription termination signals, as demonstrated for respiratory syncytial virus (51,52) and recently for EBOV (53). In our study, the abundance of the eGFP mRNA was lower than that of the downstream genes at both time points.…”
Section: Resultssupporting
confidence: 74%
“…Even though the gradient of transcription is believed to be universal for nonsegmented negative-strand viruses (50), the levels of transcription of individual genes may not necessarily follow the gradient exactly due to the regulatory role of different elements of gene junctions, which may be different for different pairs of genes. The elements, which effect transcription, include intergenic regions and transcription termination signals, as demonstrated for respiratory syncytial virus (51,52) and recently for EBOV (53). In our study, the abundance of the eGFP mRNA was lower than that of the downstream genes at both time points.…”
Section: Resultssupporting
confidence: 74%
“…Consequently, changes to the IR sequence or length have dramatic effects on gene expression in these viruses (reviewed in reference 1). In contrast, previous analyses with EBOV showed that the IRs are not essential for transcription of the adjacent genes (6,22). However, specific truncations of the 144-nt-long IR to 10, 20, or 30 nucleotides significantly inhibited downstream mRNA synthesis, while shorter or longer IRs did not result in substantial attenuation (6).…”
Section: Importancecontrasting
confidence: 64%
“…In contrast, previous analyses with EBOV showed that the IRs are not essential for transcription of the adjacent genes (6,22). However, specific truncations of the 144-nt-long IR to 10, 20, or 30 nucleotides significantly inhibited downstream mRNA synthesis, while shorter or longer IRs did not result in substantial attenuation (6). This finding is in contrast to reports for other viruses with variable IRs showing that either IR length did not influence downstream gene expression (23)(24)(25) or elongation of the IR proportionally reduced reinitiation efficiency (26).…”
Section: Importancementioning
confidence: 57%
See 2 more Smart Citations